Situation Report: Hungary, 24 February 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Central Committee Plenum New Head of Central Committee Foreign Affairs Section Janos Peter Visits Three Countries Reaction to President Nixon's Message Hippies Sentenced for Incitement Controversial Films Gain Awards; Film Trade Achieves Favorable Balance Increased Pensions and Wages Stocktaking of Hungary's Mineral Resources Co-operatives Enterprise to Include Private Cars Hungary and the Common Market Swiss-Hungarian Co-operation in the Pharmaceutical Industry Vigorous Efforts to Increase Economic Potential of Agricultural Co-Operatives